(untitled) (Nigerian Journal of Technology, 2013)
Stiffness coefficients which in essence are elements of stiffness matrix of a uniform beam element are derived in this work from first principles using elastic curve equation and initial value method. The obtained initial value solution enables exact values of stiffness coefficients, fixed end moments and shears as well as displacement (deflection and rotation) of any given beam element under arbitrary lateral load to be evaluated.